2015
DOI: 10.1002/hep.27819
|View full text |Cite
|
Sign up to set email alerts
|

Salivary microbiota reflects changes in gut microbiota in cirrhosis with hepatic encephalopathy

Abstract: Background Altered gut microbiome is associated with systemic inflammation and cirrhosis decompensation. However, the correlation of the oral microbiome with inflammation in cirrhosis is unclear. Aim Evaluate the oral microbiome in cirrhosis and compare with stool microbiome. Methods Cirrhotic outpatients [with/without hepatic encephalopathy (HE)] and controls underwent stool/saliva microbiome analysis (for composition and function) and also systemic inflammatory evaluation. 90-day liver-related hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
245
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 277 publications
(257 citation statements)
references
References 43 publications
10
245
0
2
Order By: Relevance
“…Additionally, there is evidence that the microbiome influences progression of NAFLD, ALD, and viral hepatitis to end-stage liver disease in humans (46,47), highlighting dysbiosis as a possible common denominator in these diseases. Dysbiosis has been documented in stool, sigmoid colonic mucosa, small intestinal mucosa, ascites, liver, serum, and saliva from cirrhotic patients (4,5,7,12,(48)(49)(50), pointing toward a global mucosal immune change in cirrhosis that permits widespread change in the microbiota. In one of the first studies to look at the gut microbiome using current culture-independent techniques, Chen et al demonstrated that fecal microbiota from cirrhosis patients exhibits a relative reduction in Bacteroidetes, an increase in Proteobacteria and Fusobacteria, but change in Firmicutes compared with microbiome from healthy individuals (5).…”
Section: Gut Dysbiosismentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, there is evidence that the microbiome influences progression of NAFLD, ALD, and viral hepatitis to end-stage liver disease in humans (46,47), highlighting dysbiosis as a possible common denominator in these diseases. Dysbiosis has been documented in stool, sigmoid colonic mucosa, small intestinal mucosa, ascites, liver, serum, and saliva from cirrhotic patients (4,5,7,12,(48)(49)(50), pointing toward a global mucosal immune change in cirrhosis that permits widespread change in the microbiota. In one of the first studies to look at the gut microbiome using current culture-independent techniques, Chen et al demonstrated that fecal microbiota from cirrhosis patients exhibits a relative reduction in Bacteroidetes, an increase in Proteobacteria and Fusobacteria, but change in Firmicutes compared with microbiome from healthy individuals (5).…”
Section: Gut Dysbiosismentioning
confidence: 99%
“…A study on the influence of the oral-gut-liver axis in cirrhosis directly compared the salivary microbiome in cirrhotic patients and healthy controls to the stool microbiome and analyzed salivary inflammation and prediction of 90-day hospitalizations (7). Similar to stool, autochthonous taxa (Lachnospiraceae, Ruminococcaceae, Clostridiales Incertae Sedis XIV) were reduced, while Enterobacteriaceae was increased in the saliva in cirrhotic patients compared with healthy controls.…”
Section: Ahluwalia Et Al 2016 (56)mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, we can list generalized diseases, such as rheumatoid arthritis (Zheng et al 2015), cardiovascular disease (Ordovas and Mooser 2006), and pulmonary diseases (Scannapieco and Genco 1999), as well as brain and liver abscesses (Wagner et al 2006). Other such illnesses include gastrointestinal cancer (Meurman and Grönroos 2010), breast cancer (Laidi et al 2016), cirrhosis (Bajaj et al 2015), and diabetes (Maruyama et al 2007;Deshpande et al 2010;Farag and Gaballa 2011). More recently, links with pregnancy (Digiulio et al 2015), the human immunodeficiency virus (HIV) (Kistler et al 2015), and acquired immune deficiency syndrome (AIDS) have also been described (Zheng et al 2015).…”
Section: The Huat Microbiota and General Disordersmentioning
confidence: 99%
“…Systemic endotoxemia, typically originating from the gut, is associated with liver damage, progression of liver disease, and cirrhosis decompensation. Bajaj et al (1) suggest an additional role of oral microbiota toward the overall endotoxemia and systemic inflammation in cirrhosis.…”
Section: To the Editormentioning
confidence: 99%